Classificação de dados utilizando algoritmos genéticos e lógica difusa - KATO, Rodrigo Bentes (Universidade Federal do Pará, 2013)
Several of the traditional techniques of Data Mining have been applied successfully and others have some limitations. Both, in performance and the quality of knowledge generated. Recent research has shown that the techniques in the field of IA, such as GA and Fuzzy sets, can be used successfully. In this research we are interested in investigating the applicability of a hybrid combination of genetic algorithms and fuzzy sets to find rules in large and complex spaces. This paper presents a Genetic Algorithm (GA), using Fuzzy Logic, for coding, assessment and reproduction of chromosomes, looking for classifying data using extracted rules for the automatic way with the evolution of chromosomes. The Fuzzy Logic is used to make the rules clearer and closer to human language, using linguistic representations to identify continuous data.